Incidence of malarial infection and response to antimalarial drugs at Districts Lower Dir and Swat of Khyber Pakhtunkhwa, Pakistan - Nasib Zaman; Faiz Ul Haq; Zafran Khan; Wajahat Uallah; Daniya Ualiyeva; Yasir Waheed; Muhammad Rizwan; Raja Tahir Mahmood; Majid Mahmood (Elsevier, 2022)
Malaria is the leading cause of mortality and morbidity all over the world. Several antimalarial drugs are available for the treatment of malaria. The main objective of this study was to investigate the incidence of malarial infection and the use of prescribed antimalarial drugs. A cross-sectional study was carried out to collect quantitative data from selected sites in District Lower Dir and Swat of Malakand Division Khyber Pakhtunkhwa (K.P.), Pakistan. Screening of selected patients was performed using both thick and thin films and was observed with the help of a light microscope. In this study, a total of 2517 blood samples were tested. Overall positive infection was 12% Plasmodium vivax (99.07%) and Plasmodium falciparum (0.92%). Our results evaluate that infection with Plasmodium vivax was higher than Plasmodium falciparum. No other Plasmodium species or mixed infections were observed. The rate of infection was more frequent in males as compared to female patients. The highest percentage was recorded in the summer season (35.07%), while the lowest was documented in the winter (11.7%). Out of 325 patients, 311 (95.7%) were treated with Chloroquine, and the remaining were treated with Artemether. Chloroquine was used as a drug of choice for Plasmodium vivax infection. The present study concludes that Plasmodium vivax and Plasmodium falciparum are the two common agents for malaria in Malakand Division. However, Plasmodium vivax was dominant over Plasmodium falciparum. The infection rate was high in males from District Lower Dir during the summer season.